A guide to results and diagnostics within a STRmix™ report. Issue 6 (7th July 2019) - Russell, Laura; Cooper, Stuart; Wivell, Richard; Kerr, Zane; Taylor, Duncan; Buckleton, John; Bright, Jo‐Anne
Abstract: Until recently, forensic DNA profile interpretation was predominantly a manual, time‐consuming process undertaken by analysts using heuristics to determine those genotype combinations that could reasonably explain a recovered profile. Probabilistic genotyping (PG) has now become commonplace in the interpretation of DNA profiling evidence. As the complexity of PG necessitates the use of algorithms and modern computing power it has been dubbed by some critics as a "black box" approach. Here we discuss the wealth of information that is provided within the output of STRmix™, one example of a continuous PG system. We discuss how this information can be evaluated by analysts either to give confidence in the results or to indicate that further interpretation may be warranted. Specifically, we discuss the "primary" and "secondary" diagnostics output by STRmix™ and give some context to the values that may be observed. This article is categorized under: Forensic Biology > Interpretation of Biological Evidence Forensic Biology > Forensic DNA Technologies Abstract : STRmix(TM) ‐ Resolve More DNA Mixtures.